Government Procurement and Changes in Firm Transparency - Samuels, Delphine (The Accounting Review, 2021)
ABSTRACT The government requires its suppliers to have certain internal information processes to reduce uncertainty about their ability to fulfill their commitments. I argue that these requirements improve suppliers' internal information, which leads to better external reporting. Using a dataset of U.S. government contracts, I find a positive relation between government contract awards and firms' external reporting quality. Consistent with procurement-related requirements driving this relation, I find that firms improve their external reporting when they begin contracting with the government, and that the magnitude of the improvement varies predictably with contract characteristics imposing greater requirements on contractors' internal information processes. Finally, I use the establishment of the Cost Accounting Standards Board in 1970 as a shock to contractors' internal information requirements, and find greater improvements in external reporting among firms subject to the CASB. Overall, these results suggest that the government as a customer contributes to shaping firms' information environments.